The analgesic effect of the GABA-agonist THIP in patients with chronic pain of malignant origin. A phase-1-2 study. - Kjaer, M (1983)
Fourteen patients with chronic pain of malignant origin were treated with escalating doses of THIP intramuscularly 5-30 mg in an open phase 1 study. Analgesic activity was demonstrated in 60% of the patients at the level of 20 mg THIP and a dose response relation was present. Side effects, sedation, dizziness, euphoria, nausea, and blurred vision were present in up to 80% of the patients and were dose limiting. The maximum serum concentration was reached within 1 h after dosing in 87% of all administrations. Mean t1/2 was 1.52 +/- 0.63 h and the clearance was 0.49 +/- 0.181 min. Significant correlations were demonstrated between serum concentration, dose of THIP, analgesic effect and side effects. It is concluded that THIP cannot be used for the treatment of chronic cancer pain, not because of insufficient analgesic effect but because of unacceptable side effects.